Pro Ajax and Java Frameworks - Schutta, Nathaniel T. (Apress, 2012)
Deploying an application through a browser seemed like a much more palatable option because it would eliminate the need to install software on the client computer. So, like many others, our organization moved swiftly to deploying applications to the web. Despite the relative ease of deployment, web applications still had their share of issues. Most notable from a user’s perspective was the significant loss of rich interactivity provided by the user interface. Web applications were constrained to the basic set of widgets provided by HTML. Worse yet, interacting with the server required a complete refresh of the page, which was disconcerting to users who were familiar with rich client/server applications.